2010
DOI: 10.1007/s12275-010-9369-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soil fungal communities using pyrosequencing

Abstract: Pyrosequencing, a non-electrophoretic method of DNA sequencing, was used to investigate the extensive fungal community in soils of three islands in the Yellow Sea of Korea, between Korea and China. Pyrosequencing was carried out on amplicons derived from the 5' region of 18S rDNA. A total of 10,166 reads were obtained, with an average length of 103 bp. The maximum number of fungal phylotypes in soil predicted at 99% similarity was 3,334. The maximum numbers of phylotypes predicted at 97% and 95% similarities w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 48 publications
2
64
2
4
Order By: Relevance
“…The disease generally manifests itself in young and mature plants throughout cucumber-growing stages [66]. Our study showed that Ascomycota was the dominant fungal community in the plant rhizosphere, which is contrary to previous reports [67,68]. One possible explanation for lack of disease symptoms by cucumber may be the ability of B. bacillus B068150 to out-compete the pathogen on the rhizosphere for nutrients, and establish itself as one of the dominant bacteria in the soil.…”
Section: Discussioncontrasting
confidence: 97%
“…The disease generally manifests itself in young and mature plants throughout cucumber-growing stages [66]. Our study showed that Ascomycota was the dominant fungal community in the plant rhizosphere, which is contrary to previous reports [67,68]. One possible explanation for lack of disease symptoms by cucumber may be the ability of B. bacillus B068150 to out-compete the pathogen on the rhizosphere for nutrients, and establish itself as one of the dominant bacteria in the soil.…”
Section: Discussioncontrasting
confidence: 97%
“…These species occur in Arctic or Antarctic seawater, algae, and glacial environments Vaz et al 2011;Buzzini et al 2012). However, most of them have also been reported from soil (Maksimova and Chernov 2004;Lim et al 2010) or associated with animals (Bruce and Morris 1973;Kobatake et al 1992;Zacchi and Vaughan-Martini 2002), including deep-sea corals and mussels (Burgaud et al 2010;Galkiewicz et al 2012). Additionally, we found two filamentous fungi of terrestrial or freshwater origin.…”
Section: Yeast Community At Helgoland Roadsmentioning
confidence: 52%
“…Across these diverse fungal groups, we suggest that increased labile C availability belowground leads to greater species richness, because all are dependent on an external organic carbon source. Whether belowground C availability directly or indirectly caused shifts in fungal species richness remains uncertain, as we did not independently manipulate belowground C. As is common at this sequencing level for soil fungi (36,38,59), our rarefaction curves did not plateau, which could create bias in species richness patterns. Further sequencing could therefore reveal additional diversity patterns.…”
Section: Discussionmentioning
confidence: 98%